22. SURCERY AND IMPROVEMENT OF QUAITY OF LIFE IN PATIENTS WITH LUMBOSACRAL SPONDYLOLISTHESIS: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2025)
Objective:  Overview of the role of surgery in improving the quality of life of patients after surgery for lumbosacral spondylolisthesis.Methods: A scoping review. Results: Out of 224 related articles, 7 studies met the selection criteria and were included in the analysis. These comprised 1 clinical trial, 5 cohort studies, and 1 cross-sectional study. All studies demonstrated that surgery significantly improved quality of life, with statistically meaningful outcomes.Conclusion: Surgery is significantly effective in improving patients' quality of life, especially in cases with long-term follow-up and severe spondylolisthesis. Assessment tools such as the ODI and SF-36 have demonstrated significant improvements in disability and quality of life after surgery.
Keywords: Scoping review; quality of life; lumbosacral spondylolisthesis.